EVALUATING THE CUSTOMER SATISFACTION ON THE SERVICE QUALITY OF TULANGAN SIDOARJO NEW MARKET PARKING - Kurnia Hadi Putra; Ita Suhermin Ingsih; Ramadhani Stevian Darmawan (Journal Innovation of Civil Engineering (JICE), 2021)
The evaluation of customer satisfaction becomes a vital aspect for investigating the satisfaction level of customer toward the parking service at Tulangan New Market. This research aimed at improving the service quality and performance of parking facilities at Tulangan New Market. It also intended for investigating the characteristic of customer who frequently use the parking facilities. To ease the data analysis, the researcher used Important Perfomance Analysis (IPA) method. The assessment upon 60 respondent concerning the satisfaction and interest was portrayed in quadrant 1, whereas quadrant 2 only had 1 point of questionnaire instrument. Quadrant 3 in the cartesian diagram only gained 2 questionnaire instrument and quadrant 4 had 8 questionnaire instrument. Accordingly, the respondents were satisfied with the performances of 8 questionnaire instrument because quadrant 4 earned the most points. The conclusion, the customers of parking felt satisfied with existing service of parking facility.